Review of Sexual Violence Against Children: Reality, Impact, and Protection Efforts - Saputri, Devita; Putri, Wulan Julianti; Kaya, Axcell Ezhalio Melvin; Saputra, Febriyan; Kadir, Syukron Abdul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The reality of sexual violence against children in Indonesia has become a serious issue that requires joint attention and action. Data shows a high number of cases, although many incidents are not reported. For example, the case in Way Serdang, Mesuji Regency, where a father had sexual intercourse with his pregnant biological child, illustrates the complexity of this problem. The impact of sexual violence on children includes profound psychological, social, and physical consequences, such as PTSD, behavioral disorders, and social stigma. Protection and prevention efforts must involve the government, child protection institutions and the community. Education, strong regulations and changing social norms are key to creating a safe environment for children. Early detection, the role of child protection institutions, and collaborative efforts across sectors are important strategies in overcoming the complex challenges of preventing sexual violence. Education and increased awareness are needed to change public perceptions, as well as investment in resources and research to support effective prevention efforts